(untitled) (Conferencea, 2022)
The article describes the general rules for the design of residential buildings, the process of their integral connection with architecture. The influence of universal factors on the architecture of all public buildings and structures: social, economic, ideological, environmental, urban planning, functional, compositional, space-planning, constructive, architectural and artistic factors.